2020
DOI: 10.3390/ijms21155564
|View full text |Cite
|
Sign up to set email alerts
|

Early Transcriptomic Changes upon Thalidomide Exposure Influence the Later Neuronal Development in Human Embryonic Stem Cell-Derived Spheres

Abstract: Stress in early life has been linked with the development of late-life neurological disorders. Early developmental age is potentially sensitive to several environmental chemicals such as alcohol, drugs, food contaminants, or air pollutants. The recent advances using three-dimensional neural sphere cultures derived from pluripotent stem cells have provided insights into the etiology of neurological diseases and new therapeutic strategies for assessing chemical safety. In this study, we investigated the neurodev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…In accordance with this, the Bayesian network showed that the node of TP53 was located at the top of the network hierarchy, and the strongest connection was observed between TP53 and AURKB ( Figure 5 B). The Bayesian network represents the joint posterior probability distribution over the whole set of variables in a system and is considered more biologically interpretable because of the removal of indirect correlations [ 36 ]. Intriguingly, upstream regulator analysis, the causal analytics algorithms in IPA, revealed that TP53 was the only upstream transcription regulator of AURKB, whose expression was regulated by PDMP in JHH7 cells ( Figure S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with this, the Bayesian network showed that the node of TP53 was located at the top of the network hierarchy, and the strongest connection was observed between TP53 and AURKB ( Figure 5 B). The Bayesian network represents the joint posterior probability distribution over the whole set of variables in a system and is considered more biologically interpretable because of the removal of indirect correlations [ 36 ]. Intriguingly, upstream regulator analysis, the causal analytics algorithms in IPA, revealed that TP53 was the only upstream transcription regulator of AURKB, whose expression was regulated by PDMP in JHH7 cells ( Figure S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Extensive toxicological evaluations reveal that the use of THD by expectant mothers is associated with severe congenital malformations in offspring, such as thumb loss, limb dysplasia, neurodevelopmental retardation, and congenital heart disease 31 . Several stem cell-based models have previously been utilized to investigate the effects of THD 37,[49][50][51] ; However, most of these models lack the crucial spatiotemporal and morphological context of the developing embryo. Furthermore, the precise effects of THD on early embryonic development of human remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…To perform a computational toxicity assessment using the chemical structure of the components contained in foods is the same as ascertaining a quantitative structure-activity relationship (QSAR) using the information of the chemical structural formula as a parameter. Evaluation by computational toxicology is energetically underway for environmentally hazardous substances and drug candidate substances (1).…”
Section: Introductionmentioning
confidence: 99%